The identification and expression pattern of the sex determination genes and their sex-specific variants in the egg parasitoid Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae) - Ning, Su-Fang; Huo, Liang-Xiao; Lv, Lin; Wang, Ying; Zhang, Li-Sheng; Che, Wu-Nan; Dong, Hui; Zhou, Jin-Cheng (Frontiers in Physiology, 2023)
Introduction:Trichogramma wasps are egg parasitoids of agricultural lepidopteran pests. The sex of Trichogramma is determined by its ploidy as well as certain sex ratio distorters, such as the endosymbiotic bacteria Wolbachia spp. and the paternal sex ratio (PSR) chromosome. The sex determination systems of hymenopterans, such as Trichogramma spp., involve cascades of the genes transformer (tra), transformer-2 (tra2), and doublesex (dsx) and are associated with sex-specific tra and dsx splicing. First, these genes and their sex-specific variants must be identified to elucidate the interactions between the sex ratio disorders and the sex determination mechanism of Trichogramma. Methods: Here, we characterized the sex determination genes tra, tra2, and dsx in Trichogramma dendrolimi. Sex-specific tra and dsx variants were detected in cDNA samples obtained from both male and female Trichogramma wasps. They were observed in the early embryos (1–10 h), late embryos (12–20 h), larvae (32 h and 48 h), pre-pupae (96 h), and pupae (144 h, 168 h, 192 h, and 216 h) of both male and female T. dendrolimi offspring. Results: We detected female-specific tra variants throughout the entire early female offspring stage. The male-specific variant began to express at 9–10 h as the egg was not fertilized. However, we did not find any maternally derived, female-specific tra variant in the early male embryo. This observation suggests that the female-specific tra variant expressed in the female embryo at 1–9 h may not have originated from the maternal female wasp. Discussion: The present study might be the first to identify the sex determination genes and sex-specific gene splicing in Trichogramma wasps. The findings of this study lay the foundation for investigating the sex determination mechanisms of Trichogramma and other wasps. They also facilitate sex identification in immature T. dendrolimi and the application of this important egg parasitoid in biological insect pest control programs.